A modified open surgical revision technique for malfunctioning peritoneal dialysis catheter - Shilong Xiang; Xiaohui Zhang; Yaomin Wang; Guangjun Liu; Xishao Xie; Fei Han; Jianghua Chen (Renal Failure)
Backgrounds: The malfunction of peritoneal dialysis (PD) catheter is still an intractable problem. A modified open surgical revision technique with suturing fixation and without catheter removal for malfunctioning catheter was developed to evaluated the efficacy and safety between simultaneous catheter replacement technique.Methods: A total of 167 PD patients with malfunctioning catheter were retrospectively reviewed. For the salvage of PD catheters, patients underwent modified open surgical revision (group A) or simultaneous catheter replacement (group B). The baseline characteristics before operation, perioperative condition, complications and outcomes were compared between both groups.Results: Patients of group A showed significantly shorter operative time (67.4 ± 22.1 versus 82.8 ± 21.1 min, p = 0.009), less postoperative pain score within 24 h (median 0.0 versus 2.0, p < 0.001), quicker start of PD (1.06 ± 0.31 versus 1.89 ± 0.89 days, p < 0.001), shorter length of stay (9.89 ± 5.11 versus 12.55 ± 7.37 days, p = 0.020) than group B. In terms of complications, the incidence of recurred catheter malfunction in group A was significantly lower than those in group B (1/114 versus 12/53, p < 0.001). There were no significant differences in mechanical complications (bloody effluent, dialysate leakage, and hernia) and early peritonitis between the groups. The group A patients had a favorable catheter survival rate compared with group B (log-rank, p = 0.004).Conclusions: Our modified open surgical revision technique is a safe, simple and fast method, and offers a better outcome with minimal risk of recurrence of catheter malfunction without additional cost and equipment. This technique is worthy of clinical application.